Analysis of The Impact of Financial Literacy and Financial Behavior on Millennials' Investment Decisions - Agung Hudaya; Fathihani Fathihani; Riska Rosdiana (Management Department Universitas Islam Negeri Sumatera Utara, 2021)
The pattern of consumer behavior in today's society has shifted especially financial background. This study examines the impact of financial literacy and financial behavior on investment decisions with qualitative methods and uses a descriptive, comprehensive way of static analysis. Questionnaire techniques obtained the primary data on 100 respondents, millennials aged 18-39. The data is analyzed using Multiple Linear Regression Analysis with SmartPLS. All data Instruments will be tested using validation and reliability testing. The results show that financial literacy and financial behavior significantly positively impacted millennial investment decisions. Millennials need to increase confidence in understanding financial literacy and financial behavior in determining investment decisions.Keywords: Financial behavior, financial literacy, investment decisions